2011
DOI: 10.1016/j.biopsych.2011.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind Skills Are Related to Gray Matter Volume in the Ventromedial Prefrontal Cortex in Schizophrenia

Abstract: Background Among individuals with schizophrenia, deficits in theory of mind (ToM) skills predict poor social functioning. Therefore, identifying the neural basis of ToM may assist the development of treatments that improve social outcomes. Despite growing evidence that the ventromedial prefrontal cortex (VMPFC) facilitates ToM skills among healthy individuals, methodological challenges, such as the influence of general cognitive deficits, have made it difficult to identify the relationship between ToM processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 87 publications
6
61
1
1
Order By: Relevance
“…A study on a faux pas task in schizophrenia found a correlation of behavioral ToM deficits with reductions of GM in the orbitofrontal region (Herold et al, 2009). A correlation with the ventromedial prefrontal cortex (vmPFC) was found in another study using the same task (Hooker, Bruce, Lincoln, Fisher, & Vinogradov, 2011). Volume reductions of the ACC (Fujiwara et al 2007) and the PFC (Hirao et al, 2008;Yamada et al, 2007) have been associated with poor performance in an emotion attribution task.…”
Section: Impact Of Gray Matter Reductions On Theory Of Mind Abilitiesmentioning
confidence: 96%
See 1 more Smart Citation
“…A study on a faux pas task in schizophrenia found a correlation of behavioral ToM deficits with reductions of GM in the orbitofrontal region (Herold et al, 2009). A correlation with the ventromedial prefrontal cortex (vmPFC) was found in another study using the same task (Hooker, Bruce, Lincoln, Fisher, & Vinogradov, 2011). Volume reductions of the ACC (Fujiwara et al 2007) and the PFC (Hirao et al, 2008;Yamada et al, 2007) have been associated with poor performance in an emotion attribution task.…”
Section: Impact Of Gray Matter Reductions On Theory Of Mind Abilitiesmentioning
confidence: 96%
“…However, previous research that correlates ToM functions to GM regions has focused on more controlled, on-line mentalizing tasks (Hooker et al, 2011;Russell et al, 2000).…”
Section: Impact Of Gray Matter Reductions On Theory Of Mind Abilitiesmentioning
confidence: 99%
“…This finding has been reported in several studies (e.g., see Andrews et al, 2013;Fujiwara et al, 2008;Gizewski et al, 2013;Montag et al, 2012a), but results across studies have yet to be metaanalyzed. Studies examining the fantasy component, on the other hand, report more disparate findings, with some finding significant deficits in schizophrenia samples (Derntl et al, 2012b;Fujiwara et al, 2008;Hooker et al, 2011;Lee et al, 2010) while others find fantasy abilities to be intact or trending toward greater levels in schizophrenia groups (Fischer-Shofty et al, 2013;Matsumoto et al, 2015;McCormick et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of ToM, the MPFC, orbital frontal cortex (OFC), and ACC are the main frontal areas that have been implicated in mental state attribution. Poor performance on cognitive and affective ToM tasks have been associated with reduced gray matter volumes in ventromedial PFC and ventrolateral PFC, respectively (Hirao et al, 2008;Hooker et al, 2011). The studies that have investigated functional activity in patients during different ToM tasks have consistently revealed aberrant activation patterns in the MPFC, but at the same time reflecting contrasting degrees of activation, with some demonstrating a hypoactivation (Brunet et al, 2003;Lee et al, 2006;Walter et al, 2009) and others reporting hyperactivation (Andreasen et al, 2008;Lee et al, 2010;Lee et al, 2011;Pedersen et al, 2012).…”
Section: Neuroimaging Of Theory Of Mindmentioning
confidence: 96%